2019
DOI: 10.1186/s12887-019-1526-3
|View full text |Cite
|
Sign up to set email alerts
|

Asthma medication in children who are overweight/obese: justified treatment?

Abstract: Background The prevalence of asthma and obesity have increased over the last decades. A possible association between these two chronic illnesses has been suggested, since the prevalence of asthmatic symptoms rises with increasing Body Mass Index (BMI). However, asthma is only one of several possible causes of shortness of breath in obese children. The aim of this study is to evaluate the prevalence of overtreatment with asthma medication in a cohort overweight/obese children with respiratory sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…Al-ayed et al (2019) No estudo da comparação das citocinas em pacientes asmático controlados e descontrolados, os pacientes descontrolados apresentaram níveis maiores de citocinas. Lentferink et al (2019) No diagnóstico da asma a maioria dos pacientes só tinha o diagnóstico clínico e quando associados com a espirometria poucos tinham resultado na espirometria alterado. Pasic et al (2016) Em análise de parâmetros na espirometria pacientes obesos apresentaram mais resultados alterados.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Al-ayed et al (2019) No estudo da comparação das citocinas em pacientes asmático controlados e descontrolados, os pacientes descontrolados apresentaram níveis maiores de citocinas. Lentferink et al (2019) No diagnóstico da asma a maioria dos pacientes só tinha o diagnóstico clínico e quando associados com a espirometria poucos tinham resultado na espirometria alterado. Pasic et al (2016) Em análise de parâmetros na espirometria pacientes obesos apresentaram mais resultados alterados.…”
Section: Resultsunclassified
“…O aumento de peso também influencia nos aspectos espirométricos como a redução do volume expiratório forçado no primeiro minuto e a capacidade vital forçada. Soma-se que a asma associada com a obesidade causa resposta insatisfatória na terapia adequada, no controle da asma piorando os sintomas encontrados nessas doenças (PASIC et al, 2016;LENTFERINK et al, 2019).…”
Section: Artigounclassified
“…Obesity patients are in a state of chronic inflammation. 40 Upregulation of inflammatory cytokines in obesity patients may activate the NF-κB signaling. In obese mouse models, activation of NF-κB signaling fed HFD for 12 weeks is approximately 3.5-fold than that of the baseline level.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the RANTES level in obesity‐related asthma induced by HDM or OVA was attenuated by reticuline, which might be related to the reduction in p38 phosphorylation by reticuline. Obesity patients are in a state of chronic inflammation 40 . Upregulation of inflammatory cytokines in obesity patients may activate the NF‐κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the lower efficacy in obesity-related asthma is the overuse of asthma medications in more than 25 percent of patients ( Di Genova et al., 2018 ). Some studies have shown obesity has no effect on response to omalizumab treatment; in other studies, obesity may reduce the effectiveness of omalizumab in terms of exacerbating asthma control scores, rescue therapy, and lung function ( Sposato et al., 2018 ; Lentferink et al., 2019 ). Mepolizumab has an effect on the treatment of obesity-related asthma, especially in those with early-onset asthma ( Ortega et al., 2014 ).…”
Section: Status Of Medication For Obesity-related Asthmamentioning
confidence: 99%